Perceived financial and operational impact of E-HRM in Saudi Arabia - Alharbi, Samar S. (Edelweiss Applied Science and Technology, 2025)
Currently, electronic Human Resource Management (e-HRM) encompasses various key transactional activities—such as managing employee performance, compensating staff, offering training, and handling recruitment. These combined efforts noticeably boost an organization’s overall success. This study sets out to examine, in depth, how e-HRM impacts operational efficiency within Saudi Arabian companies. A deductive and quantitative approach was adopted by distributing structured questionnaires to a random sample of 245 participants, with data analyzed using descriptive and regression techniques. The results show a robust positive link between e-HRM practices, employee performance, and HRM effectiveness, all working together to enhance organizational performance. Furthermore, the findings indicate that businesses effectively deploying e-HRM realize significant financial benefits, chiefly through better cost management and lower administrative expenses. On a practical level, these findings offer helpful guidance for managers and supervisors eager to elevate organizational efficiency by strategically implementing e-HRM systems.